The Impact of the Communist Regime in Albania on Freedom of Religion for Albanians - Tokrri, Renata; Tafani, Ismail; Shkembi, Aldo (Mediterranean Journal of Social Sciences, 2021)
The multi religions Albania passed last century from a country where atheism was the constitutional principle in a country where the basic card guarantees not only the freedom of religion but also the freedom from religion. Today, in order of guaranteeing the freedom of belief, the Constitution of Republic of Albania expresses principles which protect the religious freedom, starting from its preamble. Indeed, the preamble has no legal force but stated goals and assists in the interpretation of provisions. The spirit, with which the preamble stated, is that of tolerance and religious coexistence, in a vision where the people are responsible for the future with faith in God or other universal values. This statement reinforces the principle of secularism of the state where the latter appears as the guarantor of religious freedom by knowing in this perspective the beliefs that "sovereign" could have and can develop. In this context, the real guarantee is given to us by Article 24 of the Constitution which expressly guarantees the freedom of conscience and religion, in a perspective where any person has the right to choose if changing or not his religion or belief, so that this article appears not only as a guarantor of freedom of religion but also as a guarantor of freedom from religion. In a context like that of Albania, where for 40 years the religious freedom has been denied, and because of religious beliefs was conducted genocide, cannot be missing in its Constitution this freedom. Today it appears more consolidated than ever, from a vision that guarantees such as the freedom to choose and change religion by manifesting them freely in public or in private life, into a vision that guarantees also negative freedom or atheism. The purpose of this paper is to point out that otherwise than the socialist Constitution of 1976- which provided anti-religious atheism forms in a context where the faith was determined by the state, based in a "monotheistic" ideology and realized through policy, which denied any type of faith beyond what the material world of communist ideology had in foundation- the current one appears, secular and neutral in matters of religious faith by guaranteeing a as consequence the atheist beliefs as well. Received: 21 November 2020 / Accepted: 11 January 2021 / Published: 17 January 2021